2010
DOI: 10.2214/ajr.09.4128
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI Evaluation of Pituitary Macroadenoma: Imaging Features Predictive of Successful Transsphenoidal Surgery

Abstract: Macrocystic and macrohemorrhagic adenomas and solid tumors with enhanced diffusivity are more likely to be successfully managed with transsphenoidal hypophysectomy. Transsphenoidal hypophysectomy of solid, enhancing tumors with restricted diffusion is more likely to fail, possibly because of the greater reticulin content of the tumor; initial transcranial surgery may be appropriate in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 30 publications
(35 reference statements)
6
88
2
1
Order By: Relevance
“…The application of DWI for the evaluation of pituitary adenomas however, is limited. Prior studies evaluating the role of ADC in the assessment of adenoma consistency for preoperative evaluation are conflicting [16][17][18]. Furthermore, there is minimal literature available regarding the use of The use of ADC in this study further helped delineate a subgroup of adenomas not identified on conventional MRI sequences.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The application of DWI for the evaluation of pituitary adenomas however, is limited. Prior studies evaluating the role of ADC in the assessment of adenoma consistency for preoperative evaluation are conflicting [16][17][18]. Furthermore, there is minimal literature available regarding the use of The use of ADC in this study further helped delineate a subgroup of adenomas not identified on conventional MRI sequences.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, the ADC value is often correlated with tumor cellularity and tumor grade [14]. Furthermore, multiple prior studies have demonstrated the role of DWI in the evaluation of pituitary adenomas, ranging from preoperative assessment of tumor consistency to correlation of ADC with the proliferative marker MIB-1 [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,14 In the present study, we also performed histologic examinations by use of Masson trichrome staining. Our results indicate that the collagen content in hard macroadenomas is higher than that in soft adenomas, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to predict pituitary macroadenoma tumor consistency by use of conventional MR imaging techniques. [5][6][7] However, the ability of MR images to predict pituitary macroadenoma consistency is controversial. 8 FIESTA can provide strong T2 contrast, emphasizing the water content signal, including CSF.…”
mentioning
confidence: 99%
“…We found no significant difference between tumor to normal white matter T2-weighted signal intensity and tumor consistency during surgery. Authors suggested that this discrepancy among results could be due to the effect of various factors on the T2-weighted signal intensity including tumor cellularity, nuclear to cytoplasmic ratio, free water in the extracellular space, and cystic component in the tumor (14,15). High cellularity with a high nuclear to cytoplasm ratio and high collagen content can decrease signal intensity, whereas high extracellular free water increases SI on T2-weighted images (16 consistency.…”
Section: Discussionmentioning
confidence: 99%